2017
DOI: 10.1021/acsnano.7b00638
|View full text |Cite
|
Sign up to set email alerts
|

Nonmagnetic Quantum Emitters in Boron Nitride with Ultranarrow and Sideband-Free Emission Spectra

Abstract: Hexagonal boron nitride (hBN) is an emerging material in nanophotonics and an attractive host for color centers for quantum photonic devices. Here, we show that optical emission from individual quantum emitters in hBN is spatially correlated with structural defects and can display ultranarrow zero-phonon line width down to 45 μeV if spectral diffusion is effectively eliminated by proper surface passivation. We demonstrate that undesired emission into phonon sidebands is largely absent for this type of emitter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
163
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(190 citation statements)
references
References 52 publications
(97 reference statements)
21
163
1
1
Order By: Relevance
“…In this section, we review magneto-optical studies on SPEs in h-BN. Traditionally, non-magnetic SPEs involving singlet ground states, possibly intrinsic to a single defect or else from spin-coupled adjacent paired defects, have been associated as possible Group 2 emitters 37,112 . A recent study also reported no change in the optical spectra of h-BN defects with the application of a magnetic field 112 .…”
Section: Magnetic States For Quantum Device Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we review magneto-optical studies on SPEs in h-BN. Traditionally, non-magnetic SPEs involving singlet ground states, possibly intrinsic to a single defect or else from spin-coupled adjacent paired defects, have been associated as possible Group 2 emitters 37,112 . A recent study also reported no change in the optical spectra of h-BN defects with the application of a magnetic field 112 .…”
Section: Magnetic States For Quantum Device Applicationsmentioning
confidence: 99%
“…Categorisation of visible SPEs in h-BN into two broad groups33,37,85 . Group 2 emitters have also been observed37 with PSB intensities under 2% of the ZPL, suggesting that " < 0.25 and " > 0.8.…”
mentioning
confidence: 99%
“…While the width remains quite stable at an average value of 0.28±0.03 nm, the peak center shifts from 630.4 nm to 630.7 nm during the experiment. Spectra measured as a function of time (see Supplementary Material) indicate that this shift is a consequence of spectral and intensity fluctuations (spectral diffusion) probably caused by aleatory changes in the ionization state of nearby charge traps like shallow impurities or defects [15,34,35,36,37]. These fluctuations are also responsible for the relatively broad emission line and for the partial deviation of the line shape from that of a single peak.…”
Section: Fig 1 (A) Schematic Diagram Of the Samples They Contain Tmentioning
confidence: 99%
“…Most relevant to this work, is the ability of hBN to host atomic impurities (or point defects), that give rise to quantized optical transitions, well below its bandgap. 5,6 hBN colour centres are ultrabright with narrow and tuneable linewidth, [7][8][9] and photostability up to 800 K. 10 Whilst the nature of many of the defects is still uncertain, [11][12][13][14][15] they are being extensively studied as promising candidates for quantum photonic applications requiring on-demand, ultrabright single-photon emission. A step forward, which will significantly extend the functionality of hBN emitters for quantum applications, is to interface their optical properties with spin transitions, and realise spin-polarization and optical spinreadout schemes.…”
mentioning
confidence: 99%